Pulmonary Artery Catheter Induced Ventricular Fibrillation In A Patient Undergoing Retroperitoneal Mass Excision: Report of a rare case - Datt, Vishnu; Dahiya, Priyanka; Yadav, Simran; Kaushik, Priyanka; Dhingra, Sakshi; Agarwal, Samya; Khatri, Shreya; Gangwar, Parth; Sonkar, Arpan; Singla, Shivam; Tyagi, Aanchal (Cardiology and Cardiovascular Medicine, 2025)
Pulmonary artery catheter (PAC) is a vital monitor in cardiac patients undergoing cardiac as well as noncardiac surgery. PAC remains a gold standard for monitoring several hemodynamic parameters like continuous cardiac output measurements, right ventricular end-diastolic volume, right heart pressures, pulmonary artery pressures, and pulmonary capillary wedge pressure (PCWP), and “a” wave on wedging to diagnose the significant mitral regurgitation, and mixed venous saturation, and right atrial and ventricular pacing. The PCWP helps in maintaining the adequate LV filling and avoids volume overload. Additional derived calculations from these measurements, like pulmonary and systemic vascular resistance (PVR, SVR), cardiac index (CI), stroke volume (SV), LV and RV stroke work index, oxygen delivery, and oxygen consumption, help in diagnosing the type of shock (cardiogenic vs. septic) and selection of vasoactive drugs, vasodilators, and fluid administration. Therefore, PAC utilization could be valuable in guiding the management in high-risk surgical patients. Moreover, PAC provides several hemodynamic parameters and helps in the perioperative hemodynamic management. However, the indications for PA catheterization remain controversial due to the precipitation of complications, including fatal arrhythmia. PA catheterization can be associated with arrhythmias in approximately 12.5% to 70% of the patients. The most common arrhythmia is multiple premature ventricular contractions (PVCs) and rarely VF /VT in 1% and persistent VF in 4.7% as a fatal arrhythmia. Herein, we report a case of a 53-year-old male with a massive retroperitoneal mass with severe LV dysfunction and atrial fibrillation (AF) posted for mass excision after obtaining the informed high-risk consent, who experienced multiple PVCs during PA catheterization upon reaching the RV, resulting in severe hypotension, and converted to VF during manipulation for advancing from RV to PA. After external cardiac massage, DC shock (biphasic 200 J), and administration of lidocaine (75 mg) and magnesium sulfate (2 gm), a rhythm (95 bpm) and systolic BP of 90/60 mmHg returned on the first defibrillation; however, AF persisted. The patient's hemodynamics were optimized and maintained with milrinone, dobutamine, and nitroglycerin (NTG) infusions. After resuscitation, the surgery was completed without any complications, and the patient was extubated on the table with stable hemodynamics.